CORRELATION BETWEEN STATURE AND SKULL DIMENSIONS IN THE POPULATION OF CENTRAL INDIA: A CROSS SECTIONAL STUDY (Journal of Forensic Medicine & Toxicology, 2019)
Stature has been one of the most important factors for personal identification of individuals for medico-legal purposes in Forensic Medicine. In various medicolegal cases where identification has to be established based on skeletal remains, mainly from long bones, these are based upon the fact that there is positive correlation between long bones and stature. So in the present study, attempt was made to find out correlation and to derive the regression formula for stature and skull parameters. The present study was conducted on 146 Students of Shri Shankaracharya Institute of Medical Sciences, Bhilai (CG) between 16-20 years of age group. All the parameters were calculated as range, mean, standard deviation. Standard error of mean, correlation coefficient and standard error of estimate for height, Head length and head breadth were analysed statistically. The result shows that there is a definite correlation between stature and skull dimensions of an individual.
Keywords: Stature; Correlation; Skull Dimension